Evaluation of Leptospirosis Surveillance and Response Programs: A Systematic Review - Dessy Apriyani; Sulistyawati Sulistyawati; Yuniar Wardani (Universitas Ahmad Dahlan, 2025)
Background: Leptospirosis is a zoonotic disease that poses a public health problem in various tropical countries, including Indonesia. This disease is caused by Leptospira bacteria, which can infect humans through contact with the urine of infected animals. Method: This study aims to evaluate the effectiveness of surveillance and response programs for leptospirosis in Indonesia using a systematic literature review following the PRISMA guidelines. The data used were collected from three main databases: Google Scholar, Semantic Scholar, and PubMed. Six articles met our criteria and were included in this research. Results: The results of the study indicate that the surveillance program continues to face challenges, including a shortage of trained health workers, suboptimal case reporting and recording systems, and inadequate intersectoral coordination. Although the leptospirosis mortality rate has decreased, the fluctuating case count underscores the need to improve the surveillance system and prevention efforts. Conclusion: Increasing the capacity of health workers, optimizing the surveillance system, and strengthening coordination between sectors are needed to improve the effectiveness of leptospirosis prevention and control programs in Indonesia.